Further evidence on the extent and time course of repeat missing incidents involving children: A research note. (March 2023) - Galiano López, Clara; Hunter, Jane; Davies, Toby; Sidebottom, Aiden
This study examines the extent and time course of repeat missing incidents involving children. Using data from one UK police force (n = 2, 251), we find (1) that the majority (65%) of missing incidents are repeats, (2) that a small group of repeatedly missing children (n = 43; 6%) account for a sizable proportion of all missing incidents (n=739, 33%) and (3) that the likelihood of a child going missing repeatedly is elevated in the weeks immediately following a previous missing incident. The implications of our findings for future research and for the prevention of missing incidents are discussed.